DESIGN OF APPROVAL LINE IN QUALITY ENGINEERING DEPARTMENT - Zulfa Astuti - Nim: 13413021 , Rully
PT Dirgantara Indonesia is an aircraft company in Indonesia that has core competencies in the form of design, production, assembly, and aircraft services. PT DI receives orders from consumers in the form of general specifications. In fulfilling consumer orders, all production documents have to be verified or approved at the Quality Engineering Department to ensure the product suits the specifications. Production documents are inspected and created production guide until all are approved and ready for production. Based on historical data from July 2016 to June 2017, PT DI failed to meet the target of the approval process for 7 times. Approval process is a critical process, then the smoothness and balance of work must be kept well. Workload balance will be achieved by minimizing the total idle time. Performance in existing condition has total idle time of 193,60 minutes and smoothness index value of 57.99. The design of the approval line is done using line balancing method with hierarchical assignment with the help of CPLEX software computing. The data needed are the work element data, the type of work element, the precedence diagram, the time working, and cycle time. The resulting solution is the change of work elementÃ‚Â’s grouping at the work station. Therefore, the number of workstations and required operators is reduced from 18 to 16. Performance in proposed conditions has total idle time of 75.31 minutes and smoothness index value of 34.77. In general, the proposed solution provides better results than the existing conditions.